HIBAH KEPADA AHLI WARIS TANPA PERSETUJUAN AHLI WARIS LAIN (STUDI PUTUSAN PA STABAT NOMOR 207/PDT.G/2013/PA.STB) - DEVI KUMALA (PREMISE LAW JURNAL, 2016)
Based on Compilation of the Islamic Law, giving a hibah  must be approved by the giver’s heirs and it not more than 1/3 of his property. If the other heirs feel that they are harmed, they can file a complaint to the ReligiousCourtto cancel the hibah.This is in line with Article 210, paragraph 2 of KHI.A Notary/PPAT is not responsible for an authentic certificate which has been made without the approval of one of the heirs if it is beyond his knowledge that there is another heir who does not approve of it, or the data are forged by keeping the existence of the heir secret, or one of the persons appearing is not the real person. However, if he knows that one of the heirs does not approve of it and the Notary is proved to attach falsified information, the Notarial/PPAT deed is legally cancelled and the Notary is responsible for his criminal act according to Articles 264, 266, 55 and 56 of the Penal Code. Judges’ legal consideration of the Verdict of the Religious Court No. 207/Pdt.G/2013/PA.Stb is by considering evidence that the hibah is not made authentically and the witnesses’ testimony states that hibah is not contributed to the other heirs, the consideration was that the heir has the right on the case object, based on his share. Keywords: Compilation of the Islamic Law, Hibah, Without Heirs’ Approval